Effects of a Single Session of Systemic Vibratory Therapy on Flexibility, Perception of Exertion and Handgrip Strength in Chronic Obstructive Pulmonary Disease Individuals: A Quasi-Experimental Clinical Trial - Guedes-Aguiar, Eliane de Oliveira; Taiar, Redha; Paineiras-Domingos, Laisa Liane; Monteiro-Oliveira, Bruno Bessa; da Cunha de Sá-Caputo, Danúbia; Bernardo-Filho, Mario (Journal of Clinical Medicine, 2023)
Background: Whole-body vibration exercises (WBVE), that are generated in systemic vibratory therapy (SVT), may benefit individuals with chronic obstructive pulmonary disease (COPD). This study evaluated acute effects of SVT on the flexibility, on the perception of exertion to perform the anterior trunk flexion (ATF), and on the handgrip strength (HG). Methods: Thirty-eight individuals, separated into two groups, performed a single session of SVT (five bouts, 25 Hz, 2.5 of amplitude) on a side-alternating vibrating platform (SAVP), in two postures: sitting (Sitting group-SitG, n = 21) or standing (Stand group-StandG, n = 17). In both positions, the feet were on the base of the SAVP. The HG and the AFT were performed before and after the session, and the perception of effort (RPE) was measured during the ATF. Results: The ATF in the SitG (p ≤ 0.05) and in the StandG (p ≤ 0.05) was significantly improved, but in the comparison between both groups, no significant reduction was found (p = 0.14). The RPE was not influenced by the session. A significant increase of the HG in StandG post session (33.49 ± 10.30 kgf) p = 0.03 was found, but not in the SitG (p = 0.12) or between the two groups (p = 0.55). Conclusions: SVT, in a single acute session, would be capable of promoting some functional benefits for the COPD individuals without altering the perception of exertion to perform the ATF. Trial Registration: 49219115.3.0000.5259, RBR-72dqtm.
Keywords: chronic obstructive pulmonary disease; functionality; whole-body vibration exercise